Electromagnetic interference shielding in unmanned aerial vehicle against lightning strike - Diah Permata; Menachem C. Gurning; Yul Martin; Henry B. H. Sitorus; Mona Arif Muda; Herman H. Sinaga (Universitas Ahmad Dahlan, 2019)
Electromagnetic interference (EMI) due to lightning strike in Unmanned Aerial Vehicle (UAV) became a critical issue, since it could cause a severe damaged to electronic equipment which was installed in UAV. This paper proposed a method to reduce EMI by creating shield over the body of UAV with aluminum foil with thickness 0.15mm. A standard lightning impulse-voltage generated by impulse generator was delivered to the high voltage (HV) electrode at a particular distance from UAV. Indirect effect of lightning strike was investigated by measuring induced voltage inside the compartment of UAV fuselage during flashover between the HV electrode and UAV. Flashover between the HV electrode and UAV simulated the lightning strike. The result showed that the highest voltage only 1V at UAV compartment when 150kV impulse voltage supplied to the electrode with striking area on the wing. The measured voltage was far below 100V as the insulation level of low voltage equipment inside UAV. Although the direct effect of lightning has created a burning hole on the surface aluminum foil with thickness 0.15mm, the effect was overcome by increasing the thickness to 0.3mm. The application of aluminum foil over the surface of UAV repelled the electromagnetic interference which acted as a Faraday cage. The shielding method was successfully reduced the effect of EMI.